2023
DOI: 10.1039/d2md00347c
|View full text |Cite
|
Sign up to set email alerts
|

Structural rationalization of GSPT1 and IKZF1 degradation by thalidomide molecular glue derivatives

Abstract: Thalidomide and its derivatives are molecular glues that bind cereblon (CRBN), a component of an E3 ubiquitin ligase complex, and mediate protein interactions with neosubstrates resulting in their polyubiquitination and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
3
6
0
Order By: Relevance
“…4). Pleasingly, CPD-2743 also retained IKZF1 degradation capacity, again, with weaker effects than the isoindolinone iberdomide, but similar to EM12 (DC 50 193 ± 52 nM, D max 66%) 19 in line with our original hypothesis (Fig. 4).…”
Section: Resultssupporting
confidence: 87%
“…4). Pleasingly, CPD-2743 also retained IKZF1 degradation capacity, again, with weaker effects than the isoindolinone iberdomide, but similar to EM12 (DC 50 193 ± 52 nM, D max 66%) 19 in line with our original hypothesis (Fig. 4).…”
Section: Resultssupporting
confidence: 87%
“…However, the determinative power of these MPOs was weak across much of the chemical space surveyed. The observation that CRBN ligands extend the PPI surface ( Oleinikovas et al, 2024 ), and can cause PPI relevant conformational changes ( Watson et al, 2022 ) is consistent with groups apparently distal from the common binding site influencing substrate selectivity ( Nowak et al, 2023 ; Nguyen et al, 2024 ). In studies of CRBN binders it was observed that more proteins interact than are degraded ( Sievers et al, 2018 ) an effect which may give rise to stronger selectivity in cells ( Oleinikovas et al, 2024 ).…”
Section: Glue Molecular Design Considerationssupporting
confidence: 68%
“…Recently, we demonstrated reduced off-targets with 5-substituted degraders, [24] and another recent study shows that blocking the 5-position of the phthalimide in the IMiD scaffold prevents the formation of toxic 5-OH metabolites. [25] Taken together, these data suggest that the 5-substituted phthalimide of PHOIMiD-9 reduces off-target degradation relative to pomalidomide. These results are consistent with structure-activity relationships from other studies that have found reduced off-targets profiles associated with 5-substituted degraders.…”
mentioning
confidence: 80%